مبررات التوجه شرقاً وآثاره على الاقتصاد السوري - بلول, صابر (Latakia University Journal - Economic and Legal Sciences Series, 2018)
أدت سياسة التوجه غرباً، والانفتاح على السياسات الاقتصادية الليبرالية التي تم تبنيها خلال السنوات الماضية إلى تعقد الوضع الاقتصادي في سورية، وإلى شكل غير عادل لتوزيع الثروة لمصلحة الأغنياء. وترافق ذلك مع اندلاع الأزمة وفرض العقوبات الجائرة والحصار الاقتصادي الظالم الذي فرضته الدول الغربية وحلفاؤها في المنطقة. مما انعكس سلباً على الاقتصاد السوري. من هذا المنطلق تأتي أهمية استراتيجية التوجه شرقاً التي لا تتعلق باشتراكية أو رأسمالية، وإنما بالمصلحة السورية فقط، ولاسيما أن سورية جربت الغرب كثيراً، ولم تجن منه إلا العقوبات. إن التوجه شرقاً يأتي كخيار استراتيجي على المستوى المتوسط والبعيد، لأن له انعكاساً مباشراً على مستقبل سورية في المجالات الاجتماعية والاقتصادية، فالتوجه شرقاً يأتي لتلبية متطلبات اجتماعية واقتصادية وسياسية خاصة بعد أن أثبتت دول الاتحاد الأوروبي أنها فاقدة للمصداقية، ولعل من أهم مبررات هذا التوجه هو حجم الاختلال في الميزان التجاري، لصالح الغرب، والذي أضر بالاقتصاد الوطني، ولكن يجب التأكيد أن هذا التوجه ليست قطيعة مع الغرب، فالتوجه شرقاً وإيجاد أسواق جديدة لا يلغي الأسواق الأخرى، وإنما التوسع في الأسواق والخيارات، وهذا هو التفكير الاقتصادي العقلاني والمنطقي، وهو رؤية وقراءة صحيحة لمتغيرات الاقتصاد العالمي والعلاقات الاقتصادية الدولية بشكل عام.‏ فالعالم اليوم أمام تحول عالمي بنيوي يقوم على أن البنية الصناعية والقدرات الصناعية لم تعد تتمركز في الغرب، وإنما نمت بشكل كبير في آسيا أولاً، وفي أميركا اللاتينية ثانياً. فالبحث عن الأسواق المتممة والإضافية لتصريف البضائع كمطلب تجاري واقتصادي غاية في الأهمية بغض النظر عن الظروف الطارئة أو حتى الاستثنائية. The policy of moving towards the West, and the openning to the liberal economic policies, which have been adopted during the past years, have led to the complex economic situation in Syria as well as to unjust distribution of wealth in favour of the rich. This thing happened with the start of crisis in Syria, and unfair sanctions and economic siege imposed by Western states and their allies in the region, the thing which reflected negatively on Syrian economy. For this reason, it was highly important and strategic to move Easterly regardless of dealing with what is called Socialism or capitalism, but taking into consideration the Syrian interest, only, and specially when Syria tried the West so much, but it didn't get anything, but sanctions. To compass Easterly, is regarded as strategic option on middle and far level, because it has direct reflection on the future of Syria in social and economic fields. Moving towards the East aims to meet social, economic and political needs, specially after the EU states proved to lack credibility. Therefore, one of the most important reasons of this strategy is the size of instability of commercial balance in favour of the West, the thing which caused a lot of damage to national economy. But we have to confirm that: this strategy is not to boycott our relation with the West, as moving easterly and finding out new markets do not remove and end the other markets, but seek to promote and widen the markets and choices, and this is the economic, rational, and logical thought, and it is a right vision and reading to the changes of world economy and international economic relations, in general. As The world, nowdays, experiences, structural world changes which states that: the industrial structure and capabilities are no longer centralized in the West, but, first, they grew, to a large degree, at Asia, and then, at Latin America Thus, to look for complementary and additional markets to sell goods and commodities as a trade and economic demand, is very important regardless of urgent or even exceptional circumstances.